Impact of the COVID-19 pandemic on adults with Fetal Alcohol Spectrum Disorder: linking immune function to mental health status - Bodnar, Tamara S.; Chao, Amanda; Holman, Parker J.; Ellis, Linda; Raineki, Charlis; Weinberg, Joanne (Frontiers in Neuroscience, 2023)
Prenatal alcohol exposure (PAE) is known to cause a variety of cognitive, behavioral, and neurological changes. Importantly, mental health problems are also overrepresented in individuals with Fetal Alcohol Spectrum Disorder (FASD), the group of neurodevelopmental conditions that can occur following PAE. Approximately 90% of individuals with FASD report experiencing mental health problems over their lifespan, compared to approximately 30% in the overall population. Individuals with FASD also display impairments in coping skills and increased vulnerability to stress. Here, we investigated whether the COVID-19 pandemic would have a differential impact on mental health and inflammation-to-mood associations in adults with FASD, compared to unexposed controls (no PAE). We capitalized on our pre-pandemic study examining health and immune function and invited past-participants to enroll in the current study. Participants completed mental health assessments and COVID-related questionnaires by phone. In addition, blood samples collected at baseline (pre-pandemic) were used to probe for inflammation-to-mood associations. Overall, our results indicate that lower SES was predictive of higher coronavirus anxiety scores, with no differences between adults with FASD and controls. In addition, while there were no differences in depression or anxiety measures at baseline (pre-pandemic) or during the pandemic, examination of inflammation-to-mood associations identified differential relationships in adults with FASD compared to unexposed controls. Specifically, there was a positive association between baseline neutrophil counts and both baseline and pandemic mental health scores in unexposed controls only. In addition, for unexposed controls there was also a negative association between baseline interferon-ɣ (IFN-ɣ) and pandemic mental health scores. By contrast, only adults with FASD showed positive associations between baseline interleukin-12p70 (IL-12p70), IL-8, soluble intercellular adhesion molecule-1 (sICAM-1), and soluble vascular cell adhesion molecule-1 (sVCAM-1) and pandemic mental health scores. Taken together, to our knowledge, this study is the first to examine the impact of the pandemic in adults with FASD. And while it may be too soon to predict the long-term effects of the pandemic on mental health, our data suggest that it will be important that future work also takes into account how immune function may be modulating mental health outcomes in this population.